Cryotherapy for reduction of chemotherapy-induced alopecia: use in women with breast cancer (Research, Society and Development, 2022)
The study aims to analyze the efficacy and effectiveness of cryotherapy in reducing alopecia in women with breast cancer, as well as the effects caused by it. This is an Integrative Literature Review of qualitative analysis, in order to elucidate the evidence in the literature on the use of cryotherapy during chemotherapy in breast cancer. Impacts were observed regarding social stereotypes and emotional distress due to chemotherapy-induced alopecia, and that cryotherapy is an alternative means to reduce and minimize the impacts caused by hair vasoconstriction, reducing the effects of the antineoplastic agent on the scalp. In most of the literature, the technique proved to be effective, but in some studies, adverse effects of the technique are found, such as cold, headache and injuries. In addition, there are disagreements in the literature regarding cryotherapy causing micrometastases in the scalp. It is evident that cryotherapy is favorable, mitigating the impacts on patients coping with chemotherapy, however, the relationship between cryotherapy and its ability to manifest metastasis as an adverse effect remains controversial.